Geostatistical Maps Of Malaria Patients And Their Correlation With Distribution Indicators In Southern Iran - Mehdi Shabanipoor , Maryam Kamali , Abbasali Raz , Mohammad Saaid Dayer , Igor V. Sharakhov (Migration Letters, 2024)
Malaria is a disease caused by the Plasmodium parasite, with a prevalent distribution among people in Africa and some Asian countries. Migration of people can play a significant role in the spread of malaria. This study aims to develop and investigate the geostatistical maps of malaria patients and their correlation with distribution indicators for disease management in the years 2016-2020 in southern Iran. Malaria patient data was obtained from the Ministry of Health and drawn as geostatistical maps. To achieve full understanding and alignment of the malaria patients’ distribution patterns, five indices (Taylor, Iwao, Morisita, variance-to-mean ratio, and kappa) were used. The results showed that the aggregated distribution wave obtained from the geostatistical map in 2016, 2017, and 2018 were 2, 3, and 2, respectively. The Taylor index indicated a cumulative pattern due to higher sensitivity to the clustering of distribution in 2016 and 2017, with Taylor coefficients of 1.02 and 1.07, respectively. The Iwao coefficient showed random distribution of malaria patients. Furthermore, the alignment of maps with Morisita, variance-to-mean ratio, and kappa indices indicated that in 2016 and 2017, 15% and 20% of patients were cumulatively clustered, while 85% to 80% were randomly distributed in southern Iran. The distribution pattern of malaria patients in 2019 and 2020 was random according to all indices and geostatistical maps. In general, it can be concluded that the distribution of malaria patients in southern Iran does not show a critical phase. However, considering the migration of individuals from neighboring countries, passive and active surveillance should be carried out simultaneously to identify patients in subsequent years.